Minding Marx's Mind: A Philosophical Reflection on the 'Mind' Question. Part II. Issue 3 (2nd October 2021) - Jal, Murzban
Abstract : The second part of this essay on Marx's philosophy of the mind says that one must read and understand his Economic and Philosophic Manuscripts of 1844 for a critical questioning of the postulates in the modern sciences that deal with the 'mind' question. For Marx, there is nothing called the 'mind' especially nothing called the mind that is independent of the body. Instead there is the human essence (das menschliche Wesen). The problem is that the modern sciences have an unexamined base, namely the structure of estrangement and the logic of capitalism. These 'modern sciences' of the mind range from brain sciences and behaviour psychology which reduce humanity to 'things' in a way not very different from the way that Stalin had transformed humanity into 'things'. This essay is a consequent examination of Marx's dialectical materialism with the claim of the necessity of transcending both Old Materialism and Old Idealism. The inability to not involve these double transcendences would lead to the sighting of the ghosts of the past which weigh like a nightmare on the brains of the living.